Biochemical study of striped catfish Pangasianodon hypophthalmus broodstock induced by PMSG hormone + anti‒dopamine and turmeric addition - Harton Arfah; Agus Oman Sudrajat; Muhammad Agus Suprayudi; Muhammad Zairin Junior (Jurnal Akuakultur Indonesia)
ABSTRACT